PPU, PAE : quel rôle des outils d’urbanisme dans le développement urbain durable au Québec ? - Alexandre Murer; Julien Despax; Carine Henriot; Nathalie Molines (VertigO)
This contribution examines the role of two regulatory urban planning tools in the sustainable urban development sector in Quebec (Canada). The analysis of a corpus of PPU and PAE and interviews conducted in 2021-2022 with Quebec practitioners demonstrate a political will to regain control over real estate development and highlights its main limitations: lack of precision in their prescriptions, poor transposition into enforceable regulations, complexity of operational and legal implementation, and lack of anticipation of land dynamics. PPU and PAE remain the tools of a negotiated sustainable urbanism, admittedly coercive, but never really restrictive.